2020
DOI: 10.1101/2020.07.22.216101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeated horizontal gene transfer ofGALactose metabolism genes violates Dollo’s law of irreversible loss

Abstract: Dollo’s law posits that evolutionary losses are irreversible, thereby narrowing the potential paths of evolutionary change. While phenotypic reversals to ancestral states have been observed, little is known about their underlying genetic causes. The genomes of budding yeasts have been shaped by extensive reductive evolution, such as reduced genome sizes and the losses of metabolic capabilities. However, the extent and mechanisms of trait reacquisition after gene loss in yeasts have not been thoroughly studied.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Therefore, many strains of both T. delbrueckii and T. pretoriensis contain GAL10 but no other GAL genes. This situation has also been seen in other yeasts (Haase et al, 2020), but its physiological significance is unknown.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Therefore, many strains of both T. delbrueckii and T. pretoriensis contain GAL10 but no other GAL genes. This situation has also been seen in other yeasts (Haase et al, 2020), but its physiological significance is unknown.…”
Section: Resultssupporting
confidence: 52%
“…For example, in the T. pretoriensis clusters, the intact gene upstream of GAL1 can be GAL10, GAL2 , GAL4 or MEL1 (Figure 2). Haase et al (2020) recently identified a similar fusion of two GAL clusters (one ancestral and one horizontally transferred) in N. fulvescens .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Phenotypic traits are gained and lost frequently in animals, plants, and fungi 30, 9698 . Alternatively, traits can be retained in a species by balancing selection when different lineages or populations maintain genes or even multi-locus gene networks encoding traits due to local adaptation or fluctuating conditions.…”
Section: Discussionmentioning
confidence: 99%